Associations of weight loss with obesity‐related comorbidities in a large integrated health system. Issue 12 (28th September 2021) - Mariam, Arshiya; Miller‐Atkins, Galen; Pantalone, Kevin M.; Iyer, Neeraj; Misra‐Hebert, Anita D.; Milinovich, Alex; Bauman, Janine; Mocarski, Michelle; Ramasamy, Abhilasha; Smolarz, B. Gabriel; Hobbs, Todd M.; Zimmerman, Robert S.; et al.
Abstract: Aims: To determine the health outcomes associated with weight loss in individuals with obesity, and to better understand the relationship between disease burden (disease burden; ie, prior comorbidities, healthcare utilization) and weight loss in individuals with obesity by analysing electronic health records (EHRs). Materials and Methods: We conducted a case‐control study using deidentified EHR‐derived information from 204 921 patients seen at the Cleveland Clinic between 2000 and 2018. Patients were aged ≥20 years with body mass index ≥30 kg/m 2 and had ≥7 weight measurements, over ≥3 years. Thirty outcomes were investigated, including chronic and acute diseases, as well as psychological and metabolic disorders. Weight change was investigated 3, 5 and 10 years prior to an event. Results: Weight loss was associated with reduced incidence of many outcomes (eg, type 2 diabetes, nonalcoholic steatohepatitis/nonalcoholic fatty liver disease, obstructive sleep apnoea, hypertension; P  < 0.05). Weight loss >10% was associated with increased incidence of certain outcomes including stroke and substance abuse. However, many outcomes that increased with weight loss were attenuated by disease burden adjustments. Conclusions: This study provides the most comprehensive real‐world evaluation of the health impacts of weight change to date. After comorbidity burden and healthcare utilization adjustments, weight loss was associated with an overall reduction in risk of many adverse outcomes.